Association of nutrients intake during pregnancy with the risk of allergic disease in offspring: a meta-analysis of prospective cohort studies - Hua Feng; Yan Chen; Xiujuan Xiong; Qunying Xu; Zhongwei Zhang; Qinghua Xi; Yongning Wu; Yuanan Lu (Food Science and Human Wellness)
To investigate the role of nutrients intake during pregnancy with longitudinal development of rhinitis, asthma, eczema, wheeze, and food allergy in offspring. The PubMed, Embase, and Cochrane library were searched for articles published throughout May 2022. The pooled effect estimate were presented using relative risk and calculated by the random-effects model. Twenty-three prospective cohort studies enrolling 210817 individuals were included. The risk of wheeze in offspring were lowered when high vitamin D, vitamin E, zinc, and milk intakes during pregnancy, whereas high meat intake during pregnancy could induce additional risk of wheeze in offspring. Moreover, high β-carotene and magnesium intakes during pregnancy were related to lower eczema risk in offspring, whereas eczema risk in offspring was increased for pregnant women with high intake of butter and margarine. Finally, the asthma risk in offspring could protect against for pregnant women with high intake of vitamin D and apple, whereas high folic acid during pregnancy could produce excess asthma risk in offspring. This study provides the summary evidences regarding the role of nutrients intake during pregnancy and subsequent risk of rhinitis, asthma, eczema, wheeze, and food allergy, and further effective intervention strategies should be employed to improve childhood allergic diseases.